THE IMPLEMENTATION OF TAX-IN-KIND AND GROSS-UP METHOD IN INCOME TAX ARTICLE 21 ON CORPORATE INCOME TAX AT PT MANGGALA ARYA PRATAMA - Dharmawan, Robin; Yuniarwati , Yuniarwati (Graduate Program of Universitas Tarumanagara, 2023)
Taxes are levies paid by individuals and companies to the government to fund various public programs and services.